Rapid Detection of Apixaban by a ROTEM-Based Approach and Reversibility with Andexanet Alfa or DOAC-Stop - Viktor Taune; Mika Skeppholm; Anna Ågren; Agneta Wikman; Andreas Hillarp; Håkan Wallén (TH Open, 2022)
Background A rapid test to detect apixaban treatment would be useful in acute situations such as major bleeding, urgent surgery, or in acute thrombosis. Objective This article aims to study if the viscoelastic test rotational thromboelastometry (ROTEM) can rapidly detect apixaban in whole blood using modified triggers based on factor Xa (FXa) or Russell viper venom (RVV). Method ROTEM clotting time (CT) was measured in samples from 40 patients on apixaban treatment, and in vitro in samples spiked with apixaban (20–500 ng/mL). Commercially available trigger Ex-tem was compared with modified triggers based on FXa or RVV. Reversibility of apixaban in the samples was studied; CT was measured with and without addition of DOAC-Stop or andexanet alfa, respectively, and the difference in CT was calculated (CTdiff). Results Using FXa as trigger, we detected apixaban concentrations at 20 ng/mL and above with 100% sensitivity and 100% specificity in patient samples and in vitro. Corresponding data for Ex-tem were 92% sensitivity and 100% specificity in patients, and 94% sensitivity and 100% specificity in vitro, and for RVV 97% sensitivity and 94% specificity in patients, and 97% sensitivity and 100% specificity in vitro, respectively. CTdiff data were similar. Patient sample data were obtained within 20 minutes from sampling. Conclusion Apixaban at low therapeutic concentrations was detected within 20 minutes, and with high sensitivity and specificity. A trigger based on FXa outperformed the commercial trigger Ex-tem and a trigger based on RVV. ROTEM with a FXa-based trigger is a promising method to detect apixaban bedside in acute settings.